2019
DOI: 10.1101/645143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Image-based consensus molecular subtype classification (imCMS) of colorectal cancer using deep learning

Abstract: Image analysis is a cost-effective tool to associate complex features of tissue organisation with molecular and outcome data. Here we predict consensus molecular subtypes (CMS) of colorectal cancer (CRC) from standard H&E sections using deep learning. Domain adversarial training of a neural classification network was performed using 1,553 tissue sections with comprehensive multiomic data from three independent datasets. Image-based consensus molecular subtyping (imCMS) accurately classified CRC whole-slide ima… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…It is therefore not too difficult to foresee how this may be utilised in a computationally augmented histopathology workflow enabling more precise and faster diagnosis and prognosis. Further, the ability to quantify a rich set of histopathology patterns lays out a path to define integrated histopathology and molecular cancer subtypes, as recently demonstrated for colorectal cancers 47 . Lastly, our analyses provide proof-of-concept for these principles and we expect them to be greatly refined in the future based on larger training corpora and further algorithmic refinements.…”
Section: Discussionmentioning
confidence: 94%
“…It is therefore not too difficult to foresee how this may be utilised in a computationally augmented histopathology workflow enabling more precise and faster diagnosis and prognosis. Further, the ability to quantify a rich set of histopathology patterns lays out a path to define integrated histopathology and molecular cancer subtypes, as recently demonstrated for colorectal cancers 47 . Lastly, our analyses provide proof-of-concept for these principles and we expect them to be greatly refined in the future based on larger training corpora and further algorithmic refinements.…”
Section: Discussionmentioning
confidence: 94%
“…Although deep learning-based tissue analysis is still in its early phase, few promising results have been published. For example, a recent study reported that deep learning-based molecular cancer subtyping can be performed directly from the standard H&E sections obtained from patients with colorectal cancers (CRCs)[ 13 ]. Microsatellite instability can also be predicted from the tissue slides[ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Working on molecular subtyping, the group of Koelzer using deep learning methods for the identification of Consensus Molecular Subtypes (CMS) on H&E WSI. Their work establishes the H&E image as a surrogate for the CMS group 34 .…”
Section: Discussionmentioning
confidence: 99%